(untitled) (Federal University Gusau Faculty of Education Journal, 2025)
Studies have shown that lecturer productivity in Public Polytechnics in south west Nigeria is low. Previous studies focused more on funding of universities and learning outcomes of undergraduates than in the polytechnics and less attention was on lecturer productivity of polytechnic lecturers. This study therefore, was carried out to determine the pattern of funding and lecturer Productivity in Public Polytechnics in South West Nigeria. Descriptive research design was used. Four states (Ondo, Ogun, Osun and Lagos) that have federal and state polytechnics were purposively selected, while the four federal polytechnics were enumerated and non-proportional to size technique was used to select six polytechnics in the states. Ten Bursars were purposively selected from the public polytechnics used for the study. Funding (r=0.80) questionnaires for Lecturer and Bursars respectively, while Rectors of public polytechnics were In-depth interviewed. Quantitative data were analysed using descriptive statistics. The community service ( =2.34) was low, 74.1% of lecturers did not publish in textbooks, this showed low Research Output, while Teaching Quality ( =2.68;) and lecturers’ commitment to students project supervision ( =2.85) as rated by lecturers were moderate in Public Polytechnics. Funding ( =2.14) was low. Funding enhanced lecturer productivity in public polytechnics in South West, Nigeria. Therefore, government should increase subvention and research grants to public polytechnics’ lecturers for improved productivity.